Baseline age and time to major fracture in younger postmenopausal women. Issue 6 (June 2015) - Gourlay, Margaret Lee; Overman, Robert A.; Fine, Jason P.; Ensrud, Kristine E.; Crandall, Carolyn J.; Gass, Margery L.; Robbins, John; Johnson, Karen C.; LeBlanc, Erin S.; Womack, Catherine R.; Schousboe, John T.; LaCroix, Andrea Z.
Abstract Objective This study aims to estimate the incidence of first hip or clinical vertebral fracture or major osteoporotic (hip, clinical vertebral, proximal humerus, or wrist) fracture in postmenopausal women undergoing their first bone mineral density (BMD) test before age 65 years. Methods We studied 4, 068 postmenopausal women, aged 50 to 64 years without hip or clinical vertebral fracture or antifracture treatment at baseline, who were participating in the Women's Health Initiative BMD cohort study. BMD tests were performed between October 1993 and April 2005, with fracture follow-up through 2012. Outcomes were the time for 1% of women to sustain a hip or clinical vertebral fracture and the time for 3% of women to sustain a major osteoporotic fracture before initiating treatment, adjusting for clinical risk factors and accounting for competing risks. Women without osteoporosis and women with osteoporosis on their first BMD test were analyzed separately. Results During a maximum of 11.2 years of concurrent BMD and fracture follow-up, the adjusted estimated time for 1% of women to have a hip or clinical vertebral fracture was 12.8 years (95% CI, 8.0-20.4) for women aged 50 to 54 years without baseline osteoporosis, 7.6 years (95% CI, 4.8-12.1) for women aged 60 to 64 years without baseline osteoporosis, and 3.0 years (95% CI, 1.3-7.1) for all women aged 50 to 64 years with baseline osteoporosis. Results for major osteoporotic fracture were similar. Conclusions Because of very low rates of major osteoporotic fracture, postmenopausal women aged 50 to 64 years without osteoporosis on their first BMD test are unlikely to benefit from frequent rescreening before age 65 years.